Evidence approach to checklists: critical revision of the checklist of the Adriatic Sea fishes - Kovačić, Marcelo; Lipej, Lovrenc; Dulčić, Jakov (Zootaxa, 2020)
The updated checklist of Adriatic Sea fishes with a critical assessment of each species using an evidence approach is provided. Each fish species in Adriatic Sea listed in the last published checklist and those reported in published new records not included in the most recent Adriatic checklist, have been included. Of the total of 466 fish species, the presence in the Adriatic Sea was confirmed for 444 species by at least one positive record of the species in the area, the presence of 10 species is still unconfirmed, and 12 fish species are excluded from the list. An evidence approach protocol is recommended for general use for compiling checklists of marine fishes.